ESP in Indonesian vocational high school: A need analysis of office administration students - Murdanianto; Mas Muhammad, Idris (Politeknik Negeri Jember, 2026)
Although English instruction in Indonesian vocational high schools is formally framed as ESP, teaching materials and practices often remain generic and poorly aligned with students’ occupational needs. Addressing the limited ESP needs-analysis research on Office Administration programs, particularly in regional contexts, this study examines the English learning needs of vocational high school students in South Kalimantan, Indonesia. Employing a descriptive needs-analysis design, the study involved 70 Grade X students selected through total population sampling. Data were collected using a validated questionnaire based on established ESP and needs-analysis frameworks and were analyzed using descriptive statistics. The findings indicate that students primarily require English for workplace oral communication, yet their proficiency remains at a basic level, with significant deficiencies in speaking, listening, and vocabulary mastery, as well as grammar-related difficulties in writing. These results reveal a clear mismatch between students’ communicative goals and their current language competence. The study highlights the necessity of ESP-oriented English instruction that prioritizes communicative tasks, job-related vocabulary, and functional grammar relevant to administrative contexts. The findings offer empirical guidance for curriculum design and instructional material development in vocational education.